PEMATUHAN DAN PENYIMPANGAN PRINSIP KESANTUNAN BERBAHASA MATERI TEKS TANGGAPAN DI SMPN 4 SUNGAI RAYA - Nazhifah, Aidah Sukma; Madeten, Sisilya Saman; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Language that is in accordance with norms and culture to maintain social relations is an important key in communication. Language politeness is often found in daily activities, including in the school environment. Schools have a big role in shaping students' language impressions. The family and community of course also take part and work together in supporting the role of schools in creating children's personalities who are polite in speaking. This research focuses on analyzing language impressions in learning, especially in response text material at SMP Negeri 4 Sungai Raya. This research aims to find out and understand how compliance and violations of language politeness occur at SMP Negeri 4 Sungai Raya, especially in responding discussions and creating response texts. The method used in this research is descriptive qualitative. The data collection technique used is an observation technique adapted to the proficient free-involved listening technique (SBLC) and note-taking technique. Apart from that, recording techniques were also used in this research. The data analysis techniques used in this research are data transcription, data reduction, data presentation, and drawing conclusions. The results of this research show that student interactions include the six maxims proposed by Leech, both compliance and deviation from the principles of language politeness.